2021
DOI: 10.1038/s41419-021-03390-8
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant development of pancreatic beta cells derived from human iPSCs with FOXA2 deficiency

Abstract: FOXA2 has been identified as an essential factor for pancreas development and emerging evidence supports an association between FOXA2 and diabetes. Although the role of FOXA2 during pancreatic development is well-studied in animal models, its role during human islet cell development remains unclear. Here, we generated induced pluripotent stem cells (iPSCs) from a patient with FOXA2 haploinsufficiency (FOXA2+/− iPSCs) followed by beta-cell differentiation to understand the role of FOXA2 during pancreatic beta-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 53 publications
4
25
0
Order By: Relevance
“…In contrast to our findings, deletion of Foxa2 in mouse liver does not change the expression levels of liver genes [ 19 ]; however, the expression of developmental genes is significantly altered in mouse liver lacking both Foxa1 and Foxa2 or triple Foxa1, Foxa2, and Foxa3 [ 3 , 20 ], indicating the compensatory role played by the Foxa genes and suggest the difference between mouse and human models. Our results revealed that the loss of FOXA2 was not compensated by FOXA1 and FOXA3, particularly at the MH stage during hepatocyte development as previously reported in human [ 8 ] and rodent models [ 9 , 19 ]. Taken together, our findings indicate that FOXA2 plays an essential role in hepatocyte and biliary development.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast to our findings, deletion of Foxa2 in mouse liver does not change the expression levels of liver genes [ 19 ]; however, the expression of developmental genes is significantly altered in mouse liver lacking both Foxa1 and Foxa2 or triple Foxa1, Foxa2, and Foxa3 [ 3 , 20 ], indicating the compensatory role played by the Foxa genes and suggest the difference between mouse and human models. Our results revealed that the loss of FOXA2 was not compensated by FOXA1 and FOXA3, particularly at the MH stage during hepatocyte development as previously reported in human [ 8 ] and rodent models [ 9 , 19 ]. Taken together, our findings indicate that FOXA2 plays an essential role in hepatocyte and biliary development.…”
Section: Discussionsupporting
confidence: 82%
“…In order to investigate the role of FOXA2 in the development and function of human hepatocytes, we established FOXA2 knockout iPSC models (FOXA2 −/− iPSCs) using CRISPR/Cas9 as we recently reported [ 8 ]. We further confirmed the absence of FOXA2 in HP and MH derived from FOXA2 −/− iPSCs using Western blotting and immunostaining (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-specific hapoloinsufficiency model for FOXA2 showed severe pancreatic phenotypes, with significant reduction in pancreatic progenitors and endocrine lineages. 52 …”
Section: In Vitro Modeling Of MDmentioning
confidence: 99%
“…Other described iPSC lines were generated from patients with mutations in GCK [ 144 ], PDX1 [ 13 , 155 ], KCNJ11 [ 156 ], INS [ 157 , 158 ], YIPF5 [ 159 ], GATA6 [ 160 ], WFS1 [ 161 , 162 ], TRMT10A [ 163 ], ONECUT [ 136 ], FOXA2 [ 164 ] and activating mutations in STAT3 [ 165 ]. Patient-derived iPSCs were also used to model congenital hyperinsulinism caused by ABCC8 deficiency [ 166 ].…”
Section: Genetic Basis Of β Cell Dysfunctionmentioning
confidence: 99%